Descripción de los Parámetros Seminales y Análisis del Crecimiento Bacteriano con el Método Reproductivo Artificial Eyaculado del Equino (2021)
Microbiological studies have shown that semen samples from healthy horses involved in reproductive programs such as artificial equine ejaculate have shown the presence of microorganisms such as Chlamydophila, C. burnetii and N. caninum, abortus equi, Leptospira spp., Enrlichia risticii and Streptococcus zooepidermicus , that the optimal conditions to survive can be found, causing damage to the sperm and triggering infertility processes or infections of the reproductive tract, given this fact it is a priority to know the functioning of the microorganisms isolated in the semen, to be able to diagnose and give u treatment timely pharmacological and prevent infertility due to infectious factors generated by microorganisms. Objective: To describe the seminal parameters and the bacterial growth of the ejaculate in the equine to know the methods of identification of the microorganisms. Methodology: A descriptive documentary review and compilation monograph were used, applying three methodological phases such as: 1. Identifying the peculiarities of the bacterial growth of the ejaculate in horses to determine the class of microorganisms presented. 2. Analyze the seminal evaluation methods that have been implemented in different studies at the international and national level to determine the characteristics and functionalities. 3. Determine the appropriate conditions and treatments for an effective equine reproduction of higher quality. For this, the state of the art was conceived as a basis for argumentation by the main authors of indexed articles and studies at an international and national level that were fundamental to describe and analyze the seminal parameters and analysis of the bacterial growth of the artificial ejaculate of the equine. Recommendations: Carry out a constant reproductive evaluation of stallions before the start of the reproductive season, implement methods for the identification of microorganisms and the use of pharmacological treatments. Conclusions: Semen is contaminated in the collection process using an artificial vagina because the method increases the growth of bacteria in the foreskin and in the urethra of males, which causes a mixed flora to grow with a predominance of saprophytic bacteria such as E. coli, Streptococcus, Staphylococcus, and Pseudomonas.